A reconstruction algorithm of service path for mobile Ad Hoc network based on SDN - Fang DONG; Ou LI; Youquan MO (Dianxin kexue)
In view of the service path reconstruction for link failure in the mobile Ad Hoc network based on SDN,a hierarchical service path reconstruction method was proposed.The timeliness of service path reconstruction was improved through the combination of reconstruction on backup and calculation.At the same time,considering the possible path conflict caused by the service path reconstruction,the criterion of comprehensive determinant reconstruction was given based on the graph theory,and it also ensured the effectiveness of reconstruction service path.